2012
DOI: 10.2337/dc11-1421
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Glycemia and Diabetic Polyneuropathy

Abstract: OBJECTIVETo test whether diabetic polyneuropathies (DPNs), retinopathy, or nephropathy is more prevalent in subjects with impaired glycemia (IG) (abnormality of impaired fasting glucose [IFG], impaired glucose tolerance [IGT], or impaired HbA1c [IA1C]) than in healthy subjects (non-IG).RESEARCH DESIGN AND METHODSMatched IG and non-IG volunteers were randomly identified from population-based diagnostic and laboratory registries, restudied, and reclassified as non-IG (n = 150), IG (n = 174), or new diabetes (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
84
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 41 publications
7
84
1
4
Order By: Relevance
“…A peripheral axonal neuropathy affecting small fibers in subjects with IGT has been described in some, but not other (Dyck et al, 2012;Eriksson et al, 1994), studies. We have previously demonstrated a significant small fiber neuropathy in skin biopsies and using corneal confocal microscopy in subjects with IGT (Asghar et al, 2014), particularly those who develop T2DM (Azmi et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…A peripheral axonal neuropathy affecting small fibers in subjects with IGT has been described in some, but not other (Dyck et al, 2012;Eriksson et al, 1994), studies. We have previously demonstrated a significant small fiber neuropathy in skin biopsies and using corneal confocal microscopy in subjects with IGT (Asghar et al, 2014), particularly those who develop T2DM (Azmi et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…We have previously provided reference values for S 2 NC, S 4 NC, S 5 NC, and S 6 NC, but other nd composite scores can be derived. 34 Attributes of nerve conduction provide an objective and reliable indication of large-fiber function and dysfunction but do not provide direct information about small-fiber function or dysfunction. To provide an objective and quantitative indication of both large and small sensory fiber involvement, we combined a composite measure of large-fiber function, i.e., S 5 NC nds, and a measure of small fibers (ENFs/mm nds), and corrected both measures for applicable variables of age, gender, and physical characteristics.…”
mentioning
confidence: 99%
“…[30] While some earlier studies have also reported similar findings, [31] these have not been confirmed by others. [32], [33] We noted a prevalence of albuminuria of 20% among newly diagnosed T2DM.…”
Section: Resultsmentioning
confidence: 99%